2020
DOI: 10.1093/molehr/gaaa081
|View full text |Cite
|
Sign up to set email alerts
|

Humanin regulates oxidative stress in the ovaries of polycystic ovary syndrome patients via the Keap1/Nrf2 pathway

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinological pathology among women of reproductive age, whereas the pathogenesis is still not fully understood. Systemic and ovarian oxidative stress (OS) imbalance is a pivotal feature of PCOS. Humanin, a mitochondria-derived peptide, has been reported to function as an antioxidant in cardiomyocytes, pancreatic beta cells and other cells, but how this function is regulated remains unclear. In this study, we investigated whether humanin expression differs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 52 publications
3
39
0
Order By: Relevance
“…Thus, high ovarian NRF2 levels following açaí treatment may be a mechanism for improved mitochondrial quality, and subsequently healthier ovarian follicles. Increased NRF2 in response to antioxidant supplementation has been reported in prior studies [ 50 , 51 , 52 ], and is likely a key mechanism by which ovarian function is improved by açaí treatment.…”
Section: Discussionsupporting
confidence: 52%
“…Thus, high ovarian NRF2 levels following açaí treatment may be a mechanism for improved mitochondrial quality, and subsequently healthier ovarian follicles. Increased NRF2 in response to antioxidant supplementation has been reported in prior studies [ 50 , 51 , 52 ], and is likely a key mechanism by which ovarian function is improved by açaí treatment.…”
Section: Discussionsupporting
confidence: 52%
“…In this study, patients with polycystic ovary syndrome were investigated, and a rat model of polycystic ovary syndrome was established. Compared with the control group, the expression of superoxide dismutase (SOD), catalase (CAT), heme oxygenase 1 (HO-1), NADPH quinine oxidoreductase 1 (NQO1), and Nrf2 in the serum, ovarian tissue, and a human ovarian cell line increased; the level of ROS and Keap1 decreased in the group that was treated with the HN analog, HNG ( 58 ). Moreover, in a mouse AD model, HNG reduced p62 expression, upregulated autophagy-activating kinase 1, restored the function of cathepsin D, and promoted autophagy in mouse hippocampus tissues.…”
Section: Hn and Oxidative Stressmentioning
confidence: 99%
“…It has been found that Nrf2 and Keap1 are necessary for increasing the expression of SOD, CAT, GPX, and GSH. HN may promote the activation of Nrf2 by inhibiting the expression of Keap1 during myocardial infarction ( 58 ). In addition, the population study found that compared with normal people, the level of humanin in patients with coronary heart disease decreased and the level of lactic acid increased, suggesting that the protective effect of humanin on cardiovascular system is through antioxidant effect ( 100 ).…”
Section: Hn Regulation Of the Redox System In Acvdmentioning
confidence: 99%
“…In a previous publication by the same group, HNG supplementation was observed to decrease body weight gain and improve ovarian morphology in a dehydroepiandrosterone (DHEA)-induced PCOS rat model ( 2 ). In the most recent publication ( 1 ), the authors report a link between humanin levels and IR in the same DHEA-induced PCOS rats.…”
mentioning
confidence: 95%
“…Humanin, is reported to be involved in metabolic processes, such as diabetes and more recently PCOS ( 2 ). Wang et al ( 1 ), report a decrease in humanin concentrations in follicular fluid from women with PCOS who also display IR, but not in non-PCOS or control patients with IR, suggesting an association between humanin, IR, and PCOS.…”
mentioning
confidence: 99%